A Comparative Study to Evaluate the Effect of Bala and Shatavari Siddha Ksheera Shirodhara and Tila Taila Shirodhara in Anidra (Insomnia) - Rani Pooja; Wetal.R.Vishakha; Gupta Arun (International Journal of Ayurveda and Pharma Research, 2022)
Anidra (Insomnia) means “na nidra abhavarthe” i.e. deprivation of sleep or disturbed sleep. It has been found that disturbed sleep or less sleep can lead to various medical conditions includes stroke, obesity, diabetes, hypertension and psychological problems etc. Treatment approach for insomnia in modern medicines includes hypnotics and sedatives which cause drug dependency and leads to ill-effects on health. In Ayurveda for the treatment of Anidra, Shirodhara (Oil dripping) procedure with different liquid media has been mentioned. This study has been designed to evaluate the effect of Shirodhara with Bala and Shatavari Siddha Ksheera and Tila oil. Aim and objectives: To compare the effect of shirodhara therapy between Bala and Shatavari Siddha Ksheera and Tila tail in Anidra.Materials and method: The study was a randomized, parallel group comparative design clinical study. Total 131 patients diagnosed as Anidra (Insomnia) as per ICD -10 criteria were slected from Outpatient and in-patient in the department of Panchakarma from Ch. Brahm Prakash Ayurveda Charak Sansthan, New Delhi. India. All the patients were randomly divided into two groups A and B. Group A (66) received Bala and Shatavari Siddha Ksheera Shirodhara. Group B (60) received Tila Taila Shirodhara for 14 days which includes shirodhara for 07 days and follow-up on 14th day. Result: In this study overall there was highly significant improvement in sign and symptoms. After treatment relief in group A was 78.99% and in Group B was 77.53%. On intergroup assessment there was no significant results were obtained. Conclusion: In this study both groups were equally effective. So, it can be concluded that procedural effect may have main role as compared to drug.